The Effects of Menstrual Cycle Phase on Elite Athlete Performance: A Critical and Systematic Review - Meignié, Alice; Duclos, Martine; Carling, Christopher; Orhant, Emmanuel; Provost, Peggy; Toussaint, Jean-François; Antero, Juliana (Frontiers in Physiology, 2021)
Background: In elite athletes, training individualization is widely recommended to optimize competitive performance. Previous studies have evidenced the impact of hormonal fluctuations on different performance parameters among women athletes. While consideration of menstrual cycle phases as a parameter in training individualization strategies is necessary, systematic evidence identifying such impacts in elite athletes should be evaluated. Objective: Systematically review publications that have investigated the link between menstrual cycle phases and performance in elite women athletes. The overarching aim is to identify whether a consensus across studies exists enabling evidence-based recommendations for training individualization depending on menstrual cycle phases. Methods: This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Three major scientific publication databases were searched from inception until November 3, 2020. Studies included focused on the influence of physiological or psychological parameters throughout at least one phase of the menstrual cycle of elite athletes. Results: A total of 780 search results was yielded and 26 references from a past bibliography were added manually. 662 papers were reviewed of which 218 studies were assessed for eligibility. Of these, only seven (1%) precisely investigated the influence of a performance or physical parameter during at least one menstrual cycle phase. These seven studies included a total of 314 elite women participants (20.58 ± 1.91 years). Three used interviews, questionnaires or prospective analyses of reports. Four conducted several performance tests or included physical measures although only two performed tests during training or before/during competition. Amongst the seven studies, five performed hormonal testing through sampling of blood, saliva or urine. The remaining relied on athletes’ menstruation diaries. The current evidence suggests a variable association between menstrual cycle and a few performance-related outcomes, such as endurance or power resistance, ligament stiffness, decision making skills, psychology or competitiveness. Conclusions: Different sports performance-related parameters are affected during the menstrual cycle among elite athletes, but the parameters themselves and the magnitude and the direction of the effects are inconclusive. Additional longitudinal and prospective studies to systematically monitor on-field performance parameters are urgently required in order to enable recommendations and training individualization in female elite athletes.